2013
DOI: 10.1155/2013/696879
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavonoid-RichFlemingia macrophyllaExtract Attenuates UVB-Induced Skin Damage by Scavenging Reactive Oxygen Species and Inhibiting MAP Kinase and MMP Expression

Abstract: In this study, we investigated the antioxidant activity and anti-photoaging properties of an extract of Flemingia macrophylla, a plant rich in isoflavonoid content. Pretreatment of fibroblasts with Flemingia macrophylla extract (FME) inhibited elastase activity, promoted the protein expression of type I procollagen, and attenuated the phosphorylation of mitogen-activated protein (MAP) kinase and the protein expression of matrix-metalloproteinase- (MMP-) 1, 3, and 9. The IC50 values were 2.1 μg/mL for DPPH radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 36 publications
(48 reference statements)
0
39
0
Order By: Relevance
“…Exposing cells to UVB irradiation can induce ROS production. ROS are known to play a key role in photoaging, triggering complex signaling pathways that result in the overexpression of MMPs or degradation of the ECM in connective tissues [26,27]. A previous study showed that macelignan, which is a natural lignan isolated from nutmeg, significantly inhibits UVB-induced increases in MMP1 expression by suppressing ROS production [28].…”
Section: Effects Of Usm Treatment On Ros Productionmentioning
confidence: 99%
“…Exposing cells to UVB irradiation can induce ROS production. ROS are known to play a key role in photoaging, triggering complex signaling pathways that result in the overexpression of MMPs or degradation of the ECM in connective tissues [26,27]. A previous study showed that macelignan, which is a natural lignan isolated from nutmeg, significantly inhibits UVB-induced increases in MMP1 expression by suppressing ROS production [28].…”
Section: Effects Of Usm Treatment On Ros Productionmentioning
confidence: 99%
“…The chemical investigation of the roots of F. philippinensis led to the isolation of three new (1-3) and twelve known compounds (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The structures of 1-3 were elucidated on the basis of their spectroscopic data.…”
Section: Discussionmentioning
confidence: 99%
“…Several species are used as ethnodrugs for a long history to cure rheumatoid arthritis, lumbocrural pain, lumbar muscle strain, swollen feet, chronic nephritis, menopausal syndrome and so on [1]. Previous chemical investigations have demonstrated that the genus is a rich source of isoflavonoids, chalcones, flavones, terpenoids, and phenolics [2][3][4][5][6], exhibiting various biological activities [5][6][7][8]. Among them, isoflavonoids are the major bioactive ingredients and have been obtained from the roots, stems, flowers and seeds of the Flemingia plants, some of which exhibit anti-cancer, antioxidant and chemical protective activities [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Western blot analysis was used to demonstrate the effects of K36E on the expression of melanogenesis-related proteins in B16F0 cells as previously described [7, 8, 22, 28, 29]. B16F0 cells were seeded in a 10-cm dish for 24 h and treated with α-MSH alone (control group) or with α-MSH plus various concentrations of K36E for 48 h. The lysates were centrifuged and the protein content was determined using a Bradford reagent (Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%